Saha Türkçesinde Suuy-, Suun – “Yu-, Yun-”, Iraas, Iraastaa-, Iraastan – “Arı, Arı-, Arıt-, Arın-” Fiilleri Üzerine Bir İnceleme - Sağlam, Mehtap Solak; Solak Sağlam, Mehtap (Marmara Türkiyat Araştırmaları Dergisi, 2023)
Sakha Turkic has always been studied in terms of its words and forms, and has provided information about the historical development of the Turkish language. It has had many variants due to the distance of its geography from the central Turkic lands and its interaction with different languages in the region throughout history. This article examines two verbs in Sakha Turkish related to the concepts of ‘clean’ and ‘to clean’ as well as other nouns and verbs that emerged in connection with these verbs. First, the Old Turkic verb yū – is examined followed by an evaluation of its meanings and uses in the historical process. It is then compared with the verb suuy-, which is the equivalent of this verb in Sakha Turkic. The verb suun-, which was derived in connection with this verb in Saha Turkic, is also compared with the Old Turkic verb yun-. The words arı-, arı(g), arıt-, arın – used in Turkish in connection with the concept of cleanliness constitute the second part of the article. The noun ıraas and the verb ıraastaa-, which were formed as the equivalent of these nouns and verbs in Sakha Turkic, were examined in terms of their meanings and usages in Sakha Turkic. The words examined in terms of sound equivalence and meaning were evaluated in this context, and the results were presented. The results demonstrate that the Sakha Turkic equivalent of the Old Turkic verb yū – is suuy-, and the Sakha Turkic equivalent of the Old Turkic arıg name is ıraas. It is noteworthy that the words Old Turkic arıg/arıt – and the Sakha Turkic equivalent ıraas/ıraastaa – are semantically different and contain more spiritual cleanliness. Saha Türkçesi bünyesinde barındırdığı kelimeler ve yapılar açısından her zaman incelemelere konu olmuş, Türk dilinin tarihsel gelişimi hakkında bilgi vermiştir. Konuşurlarının yaşadığı coğrafyanın genel Türk coğrafyasından uzak olması, tarihsel süreçte çevresindeki etkileşimde bulunduğu farklı dillerden etkilenmiş olması nedeniyle Saha Türkçesinde farklılaşmalar meydana gelmiştir. Bu yazıda “temiz” ve ...